AN INVESTMENT SUPPORT STRATEGY FOR HEAT SUPPLY, WATER-SUPPLY AND OVERFLOW-PIPE ENTERPRISES IN UKRAINE - L. Blinova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The investment necessities of heat-supply, water-supply and overflow-pipe enterprises are considered in the article. Priority measures for the search of financial sources to satisfy the investment necessities are determined. The most prior and effective financial sources for satisfaction of investment necessities of heat-supply, water-supply and overflow-pipe enterprises are analyzed. The analysis shows that the creation of regional investment funds of functioning and development of housing and public utilities as independent, non-departmental establishments is one of perspective directions in forming of additional profits for providing the concrete prior necessities of enterprises taking into account regional peculiarities. Disparity of housing services, that are supplied by heat-supply, water-supply and overflow-pipe enterprises , to modern world standards predetermine considerable wear of the fixed assets of industry